Copper (II) complexes bearing ether based ON donor bidentate Schiff bases: Synthesis, characterization, biological and electrochemical investigations. (9th March 2017) - Shabbir, Muhammad; Akhter, Zareen; Ahmad, Iqbal; Ahmed, Safeer; McKee, Vickie; Ismail, Hammad; Mirza, Bushra
Graphical abstract: Synthesis of novel ON donor ether based Schiff bases copper(II) complexes. Characterization of synthons by FTIR spectroscopy, elemental analysis and electro-analytical techniques. Biological (cytotoxic, antitumor) as well as electrochemical studies (drug–DNA interaction). Substantial interaction with DNA molecules. Abstract: Four novel copper complexes bis((E)-2-((4-phenoxyphenylimino)methyl)phenolate) copper(II) (CuL1 ), bis((E)-2-((4-(4-biphenyloxy)phenylimino)methyl)phenolate) copper(II) (CuL2 ), bis((E)-2-((4-(naphthalen-1-yloxy)phenylimino)methyl)phenolate) copper(II) (CuL3 ) and bis((E)-2-((4-(2-naphthoxy)phenylimino)methyl)phenolate) copper(II) (CuL4 ) have been synthesized and characterized by FTIR spectroscopy, elemental analysis and electro-analytical techniques. Single crystal X-ray diffraction analysis of complex (CuL1 ) revealed that the compound crystallizes in the orthorhombic crystal system. The absolute structure has been determined from the diffraction data. The molecule lies on a 2-fold axis with geometry intermediate between square planar and tetrahedral. In the complexes the ligands are bidentate, coordinating through phenolate oxygen and azomethine nitrogen to the copper ions. The biological studies (cytotoxic and antitumor) have revealed their bioactive nature. Results of brine shrimp cytotoxicity indicated their LD50 values <1 μg/ml and IC50 values from 0.7 to 16 μg/ml, indicating their antitumor nature. The voltammetric analysis showed that the complexes follow one electron transfer quasi-reversible partially diffusion controlled process. Further, the electro-reduced form of the complexes had substantial interaction with DNA molecules in a concentration dependent manner.